(untitled) (E Global Congress, 2025)
This article provides a scientifically grounded analysis of the possibilities of using amaranth flour in bakery products. The rich content of biologically active compounds in the amaranth plant, including high levels of protein, lysine, unsaturated fatty acids, and minerals, is identified as a significant factor in enhancing the nutritional and functional value of bread products. The results of the study indicate that the optimal formulation is achieved by incorporating amaranth flour at a ratio of 10–15% in combination with wheat flour. Such supplementation increases the protein content of bakery products, reduces their glycaemic index, and contributes to the prevention of cardiovascular diseases. The article highlights the physicochemical, biological, and economic advantages of amaranth flour and outlines the prospects for its industrial-scale application under the conditions of Uzbekistan.